EMPIRICAL STUDY OF SOCIO-PSYCHOLOGICAL FACTORS IN THE FORMATION OF ADDICTION BEHAVIOR IN ADOLESCENTS (Scientific journal of the Fergana State University, 2024)
This article separately studies the socio-psychological factors in the formation of addictive behavior in adolescent boys and girls, the psychological nature of the relationship between adolescent autonomy, subjective loneliness, emotional sympathy and addictive behavior as the subject of ethnopsychological scientific research. Adolescents who do not have the necessary resources of social support, acceptance and attention from their parents belong to a vulnerable group that causes the emergence of addictive behavior. Here, addictive behavior compensates for social forms and becomes an option for escaping traumatic reality. . Adolescents with addictive behavior experience significant academic difficulties, and academic difficulties cause them to avoid addictive problem behaviors, resulting in more severe learning failures. External and internal conflicts are explained as a factor that enhances addictive behavior.